PERAN KETELADANAN ORANG TUA DAN GURU DALAM MENINGKATKAN KEDISIPLINAN IBADAH SISWA DI HOMESCHOOLING ABDURRAHMAN BIN SHAKHR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyse the role of parental and teacher role models in improving student worship discipline at Abdurrahman bin Shakhr Homeschooling. The background of this study is based on the importance of role models in shaping children's religious character, especially during primary school, which is the early phase of worship habits. The research approach used was qualitative with a desk method. Data were collected through in-depth interviews, participatory observation, and documentation of teachers, parents, and students. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing using source triangulation techniques and methods to increase the validity of the findings. The results of the study indicate that the exemplary behaviour of parents and teachers has a significant influence on improving students' worship discipline, particularly in the performance of obligatory prayers, reading the Qur'an, and applying religious manners in daily life. Parental role modelling forms the basis for establishing religious habits at home, while teacher role modelling reinforces these habits in the school environment. The interplay between the two creates an educational environment conducive to the formation of religious character and religious discipline in students. This study concludes that ongoing collaboration between families and schools is essential to reinforce religious values in children from primary school age onwards. Thus, the role of parental and teacher role models can improve students' worship discipline in their daily lives.